Implementation of Moral Education for Parents from a Hadith Perspective in the Griya Yasa Housing Complex in Bekasi - Putri Mutmainah; Debibik Nabilatul Fauziah; Neng Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to determine the implementation of moral education for parents from a hadith perspective at Griya Yasa Bekasi Housing. Morals towards parents can be done by being filial to both parents. Warnings about being filial to parents are repeatedly mentioned in the Koran and hadith. However, the reality is that there are still many children who do not show their devotion to their parents. The average age of these children is 15-18 years. Therefore, this research focuses on middle adolescent children. This research uses qualitative field research methods using observation, interview and documentation data collection techniques. Interviews were conducted with six teenagers. The results of the research show that, (1) Morals towards parents from the hadith perspective include being filial to both parents, including obeying the orders of both parents, guarding their verbal (speech) and praying for both parents, prioritizing devotion to the mother, and not being disobedient to both parents. parents either in words or deeds. (2) The implementation of adolescent morals in Griya Yasa Housing, Cibitung District, Bekasi Regency towards parents is quite good. This is based on research results where when children make a mistake, they immediately realize their mistake. Then when both parents were angry, they tried to restrain themselves from behavior that could lead to disobedience and tried to melt both of their hearts. What causes children to disobey their parents is that children are busy playing with cellphones and are influenced by social environmental factors.